Using Animated Videos to Promote the Accessibility and Understandability of Package Leaflets: Retrospective Observational Study Evaluating the First Year of Implementation - Liselot N van den Berg; Niels H Chavannes; Jiska J Aardoom (JMIR Publications, 2023)
BackgroundThe medication package leaflet is the most used and trusted source of information in the home situation but is often incomprehensible for individuals, especially for those with limited health literacy. The platform "Watchyourmeds" comprises a web-based library with over 10,000 animated videos that explain the most essential information from the package leaflet in an unambiguous and simple manner to increase the accessibility and understandability of package leaflets. ObjectiveThis study aimed to investigate Watchyourmeds in the Netherlands from a user perspective during the first year of implementation by investigating (1) usage data, (2) self-reported user experiences, and (3) the preliminary and potential impact on medication knowledge. MethodsThis was a retrospective observational study. The first aim was investigated by examining objective user data from 1815 pharmacies from the first year of implementation of Watchyourmeds. User experiences (second aim) were investigated by examining individuals' completed self-report questionnaires (n=4926) that they received after completing a video. The preliminary and potential impact on medication knowledge (third aim) was investigated by examining users' self-report questionnaire data (n=67) that assessed their medication knowledge about their prescribed medication. ResultsNearly 1.8 million videos have been distributed to users by over 1400 pharmacies, with monthly numbers increasing to 280,000 in the last month of the implementation year. Most users (4444/4805, 92.5%) indicated to have fully understood the information presented in the videos. Female users reported more often to have fully understood the information than male users (χ24=11.5, P=.02). Most users (3662/4805, 76.2%) said that they did not think any information was missing in the video. Users with a lower educational level stated more often (1104/1290, 85.6%) than those with a middle (984/1230, 80%) or higher (964/1229, 78.4%) educational level that they did not seem to be missing any information in the videos (χ212=70.6, P<.001). A total of 84% (4142/4926) of the users stated that they would like to use Watchyourmeds more often and for all their medication, or would like to use it most of the time. Male users and older users stated more often that they would use Watchyourmeds again for other medication than the female (χ23=25.0, P<.001) and younger users (χ23=38.1, P<.001), respectively. Almost 88% (4318/4926) of the users would recommend the web-based library to friends, family, or acquaintances. Regarding the third aim, results showed that 73.8% (293/397) of the questions assessing users' medication knowledge were answered correctly. ConclusionsThe results of this study suggest that a web-based library with animated videos is a valuable and acceptable addition to stand-alone package leaflets to increase the understanding and accessibility of medication information.